The problems of formation of innovate potential and stimulation of innovative activity in the sphere of education (Путеводитель предпринимателя, 2020)
In the conditions of modern management the formation of innovate potential and stimulation of innovative activity in the sphere of educationact as key factors of growth, development and competitiveness. The solution to these issues would not only favour the strengthening of scientific and innovative powers in the sphere of education, but would also provide right preconditions and the basis for stable growth of present economy in Russian Fedration.